Mechanical large bowel obstruction as the initial presentation of locally advanced pancreatic tail carcinoma: a case report and literature review - Elagili, Faisal; Abd Aziz, Mohd Fahmi; Md Nor, Azmi (Beijing Clintile Information Technology (Hong Kong) Co., Limited . Supported by: Beijing Renhe Information Technology Co., Ltd., 2024)
We report a rare case of large bowel obstruction caused by locally advanced pancreatic tail adenocarcinoma. A 58- year-old male chronic smoker presented with progressive abdominal distention and absolute constipation for three weeks, without nausea or vomiting. On examination, he appeared cachectic with a grossly distended, tympanic, and tender abdomen, while rectal examination was unremarkable. A CT scan revealed diffuse bowel dilatation with a transition zone at the splenic flexure. Emergency exploratory laparotomy identified a mass involving the left colonic flexure, spleen, and pancreatic tail. The patient underwent a left hemicolectomy, splenectomy, and distal pancreatectomy, with the creation of stoma. Histopathology confirmed ductal adenocarcinoma originating in the pancreatic tail with invasion into the colon and spleen. Postoperatively, he developed hospital-acquired pneumonia, which resolved with antibiotics, and was discharged on day 21. Unfortunately, he succumbed to recurrent pneumonia with severe sepsis one week later. Although rare, pancreatic adenocarcinoma should be considered in the differential diagnosis of large bowel obstruction.